2003
DOI: 10.1063/1.1590405
|View full text |Cite
|
Sign up to set email alerts
|

Gouy phase shift of single-cycle picosecond acoustic pulses

Abstract: Ultrafast laser pulses are used to generate single-cycle picosecond acoustic pulses in thin metal films on silicon. For small initial excitation spot sizes, propagation of the acoustic pulses across a 485-m Si crystal leads to significant diffraction effects. The temporal reshaping of the acoustic wave form due to diffraction is investigated, and we demonstrate that the acoustic far field can be reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…It can be demonstrated that the detection occurs in the far-field region which simplifies the analysis of the detection pattern. 35 The transition between the near-field and the far field occurs at the depth 36 …”
Section: B Imagery Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be demonstrated that the detection occurs in the far-field region which simplifies the analysis of the detection pattern. 35 The transition between the near-field and the far field occurs at the depth 36 …”
Section: B Imagery Methodsmentioning
confidence: 99%
“…As a consequence, the spatial extension of the pulse is doubled and the shape becomes unipolar. 19 During its propagation from the near field to the far field, the acoustic pulse transforms from a unipolar to a bipolar shape 35 which explains the antisymmetric shape of the detected echo. 19 We deduce that the experimental value R of the radius corresponds to the midpoint of the perturbation seen in surface.…”
Section: Appendix A: Analyzing Ripples From Surface Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the absorbed optical power can raise the temperature of the sample so much that the attenuation is not negligible anymore. Moreover, the UAPs are also affected by diffraction [15,16]. However, previous experiments [2][3][4][5]7] mainly relied on the observation of discrete features propagating faster than the sound and whose velocities and numbers grow with initial UAP amplitude to sustain the existence of KdV solitons.…”
Section: Introductionmentioning
confidence: 99%
“…After this special nonlinear development, the pulses may again be used to excite embedded structures or surface layers on the other side of the crystal, or excite two-level systems. Finally, special far-field techniques are being developed to map out the diffraction of a reflected pulse from a nano-object [52], allowing for the full 2-dimensional reconstruction of the image.…”
Section: Coherent Phonons In Two-level Mediamentioning
confidence: 99%